The stronger impact of inorganic nitrogen fertilization on soil bacterial community than organic fertilization in short-term condition - Zhang, Meiling; Zhang, Xin; Zhang, Liyu; Zeng, Li; Liu, Yao; Wang, Xiubin; He, Ping; Li, Shutian; Liang, Guoqing; Zhou, Wei; Ai, Chao (Geoderma, 2021)
•The effect of 3-year fertilizations on soil bacterial community in 3 agroecosystems.•Geographic location was a main factor shaping soil bacterial community structure.•Short-term effect of chemical N fertilizer on bacterial community was much stronger.•N fertilizer reduced bacterial network complexity and connectivity in upland soil. Nitrogen (N) fertilization is a pivotal contributor to increasing crop yields. The substantial long-term effects of fertilization on soil microbial communities have been clearly verified. However, the short-term impacts of inorganic and organic fertilization are more stochastic and less deterministic in different agroecosystems, especially at a large spatial scale. Here, we examined the effect of 3 years of different fertilization strategies (i.e., no N fertilizer, inorganic N fertilization, and total or partial replacement of inorganic N by organic manure) on the soil bacterial community in three agroecosystem types spanning the middle temperate zone to the subtropical zone. The results showed that the main contribution to the changes in soil bacterial community structure were dominated by geographic location, which accounted for 61.60% of structural variation, while sampling season and fertilization practice explained 1.52% and 0.61%, respectively. Across three contrasting agroecosystem types, the inorganic N-alone application had greater impacts on the bacterial community structure than organic N fertilization, but the changes in composition were dependent on geographic location. Further, N fertilizer addition reduced soil bacterial network complexity and connectivity; specifically, some key module hubs belonging to non-dominant taxa were lost in N-fertilized upland soils, indicating reduced diversity and stability of the soil micro-ecosystem. Together, our results suggest that, when compared with the mild organic N source, the short-term stimulatory effect of chemical N fertilizer tended not to be beneficial for agroecosystem stability and sustainability.